USER INTEREST IN MASLAHAH-BASED MOBILE BANKING FOR MAINTAINING CUSTOMER LOYALTY - Zulika Zulika; Irwan Misbach; Nasrullah Bin Sapa; Heri Irawan; Muhammad Afif Qubais (FINANSIA : Jurnal Akuntansi dan Perbankan Syariah, 2025)
The development of digital services in Islamic banking demands alignment between technological convenience and the values of maqashid al-shariah. This study aims to identify user interest in the Muamalat DIN Mobile Banking application based on maslahah and to analyze the role of its features in building customer loyalty. The research uses a qualitative approach with a case study design grounded in Islamic consumer behavior theory and the concept of maqashid al-shariah. The results show that interest in using the Muamalat DIN application is influenced by the need for Islamic banking services, religious trust, social demands, and institutional regulatory support. The main features that drive customer loyalty include security, ease of transactions, service benefits, and the function of distributing social funds. All of these features reflect the values of maqashid al-shariah in preserving religion, wealth, and social welfare. These findings confirm that applying the principle of maslahah in mobile banking can enhance the trust and loyalty of Islamic banking customers.